The relation between education and emancipation: Something like water and oil? introducing the special issue - Southwell, Myriam Monica (2019)
This issue of Paedagogica Historica is a product of the 39th ISCHE Conference, held in Buenos Aires, from 17 to 21 July 2017. For this reason, the journal exceptionally includes articles in Spanish. At the event, 442 papers were presented, distributed in 103 sessions in which 363 participants (271 researchers and 92 students) from 36 countries of the 5 continents participated. The central theme of the Conference – also covered in this issue – was Education and Emancipation.